A Computational Approach to Source Adaptation in Thomas Malory's Morte Darthur. Issue 1 (30th December 2019) - Edlich-Muth, Christian; Edlich-Muth, Miriam
Abstract : The many source texts that late medieval adaptors like Thomas Malory worked with constitute a potential wealth of information concerning the genesis of the linguistic and stylistic features shaping their works. As a result, their texts provide a useful framework for further developing and testing methods of stylometric analysis in the context of adaptation as a collaborative form of authorship. Our interdisciplinary team has undertaken a stylometric analysis of the eight different sections of Thomas Malory's Morte Darthur, in order to identify differences between these sections and how they correspond to the language of the Old French and Middle English sources that Malory is known to have worked with in the different sections of his work. Our findings provide a basis for addressing unresolved scholarly questions concerning Malory's Morte, such as the nature of the source used for his "Tale of Sir Gareth" and whether Malory himself was responsible for the differences between the two surviving versions of his "Roman War" episode in Book II of the Morte . They further shed light on ongoing controversies concerning the overall textual unity of the Morte and the process by which Malory created the different sections of his work—an issue that lies at the heart of broader debates concerning where Malory and other late medieval adaptors are to be situated on the continuum between "faithful translator" and "original author."